Fences in our heads: a discourse analysis of the korup resettlement stalemate - Diaw, C.; Tiani, A.M. (2010)
The resettlement of people from human-inhabited protected areas (HIPAs) is a contentious point in the people-and-parks debate. This article illustrates the setbacks that can arise from conservation-and-development projects where these two realms of local reality are separated through resettlement schemes, rather than integrated. We rely on a comprehensive social, ecological, economic, and legal cost-benefit and risk analysis of the Korup National Park's resettlement program in Cameroon. After 23 years, in 2003, this program had reached a stalemate, with skyrocketing costs and near-closure of policy alternatives. The article suggests that ideology and policy combined to generate conservation failure, while inhibiting institutional learning and managers' ability to opt out of failing policies. We identify a nexus of three factors at the root of these problems: (a) legal fencing; (b) implicit policies; and (c) self-serving scientific myths. In the Congo Basin, where the architecture of protected areas was built around the tenets of "fortress conservation," legal reform is clearly needed to enable effective community conservation. We argue, nonetheless, that negotiated alternatives remain feasible even within the current legal strictures. Progress requires, however, that managers move away from past exclusionary policies and engage in genuine co-management work within HIPAs.